Disposal of Petroleum Installations - Major Policy Issues - Petter Osmundsen; Ragnar Tveterås (Center for Economic Studies and ifo Institute (CESifo), 2000)
Following the Brent Spar controversy, the OSPAR countries reached a unanimous agreement in 1998 for the future rules for disposal of petroleum installations. The vast majority of existing offshore installations will be re-used or returned to shore for recycling or disposal. For installations where there is no generic solution, one should take a case-by-case approach. We provide a survey of international economic and regulatory issues pertaining to disposal of petroleum installations, and provide specific examples by analysing the Norwegian decommissioning and disposal policy. Optimal disposal policy can be analysed by cost-benefit analyses with distributional effects, subject to environmental and goodwill constraints.
Keywords: D62; G18; H32; L51; L72; Q48; 330; Petroleum installations; decommissioning; disposal; externalities